Pengaruh kualitas batu bara terhadap produksi gas SO2 dan NOx: studi kasus PLTU “Lentera” - Hermawan, Qori Fajar; Khoirunisa, Nanda; Sihotang, Zetsaona; Riza, Muhammad; Wasono, Wasono (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
The “Lentera” power plant is a 130 MW coal-fired power plant facility. The quality of the supplied coal to the “Lentera” power plant were tested using proximate and ultimate analysis to determine sulphur and nitrogen content. The production of SO2 and NOX emissions from coal combustion was affected by the sulphur and nitrogen content in the coal. Emission levels were observed using the Continuous Emission Monitoring System (CEMS). This research was conducted to determine the effect of the sulphur and nitrogen content in coal on the production of SO2 and NOX gas at "Lentera" power plant during June-December 2020. The analysis was done based on statistical analysis using simple linear regression methods and analysis of variance. Based on the content of sulphur, nitrogen and caloric value, coal from East Kalimantan Province has a lower value than coal from South Sumatra Province. The content of sulfur and nitrogen significantly affected the production of SO2 and NOX emissions. The higher the sulfur and nitrogen content in coal showed the higher the production of SO2 and NOX emissions. The caloric value of coal did not show a correlation with the production of NOX emissions.